Family contributions to sport performance and their utility in predicting appropriate referrals to mental health optimization programmes - Hussey, J. E.; Donohue, B.; Barchard, K. A.; Allen, D. N. (European Journal of Sport Science, 2019)
Limited research has examined the contributions of sport-specific family relationship problems to athlete mental health. In the current study we examined the extent to which collegiate athletes` family problems (as measured by the Student Athlete Relationship Instrument factors, SARI) predict athletes` general mental health distress and specific mental health symptoms that are relatively common in athletes (i.e. depression, anxiety, and drug and alcohol use). The study included 85 collegiate athletes (intramural, n = 26; club sport, n = 12; NCAA Division I, n = 47). We hypothesized that both general mental health distress and commonly evidenced mental health symptoms would be predicted by athletes` responses to the SARI factors (Poor Relationship and Lack of Support, General Pressure, Pressure to Quit or Continue Unsafely, Embarrassing Comments, and Negative Attitude). Results indicated that all of the aforementioned SARI factors predicted athletes` ratings of depression and general mental health distress levels. Only the General Pressure SARI factor predicted athletes` anxiety and drug use. Alcohol use was not predicted by any of the SARI factors. Receiver operating characteristic (ROC) analyses indicated that sport-specific problems in family relationships provided a good classification of athletes at risk for general mental health distress, depression, and anxiety. Practice implications are discussed in light of the results.